(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Cybersecurity has emerged as a critical concern for the Indian banking sector, given the rapid adoption of digital technologies and the increasing sophistication of cyber threats. This study critically evaluates the challenges faced by Indian banks in maintaining robust cybersecurity measures, such as phishing attacks, malware, ransomware, data breaches, and insider threats. The research explores the key vulnerabilities within the sector, including legacy systems, inadequate cybersecurity frameworks, lack of skilled personnel, and regulatory challenges. Furthermore, it highlights possible mitigation strategies, such as enhancing cybersecurity infrastructure, adopting advanced technologies like artificial intelligence and blockchain, improving regulatory compliance, and promoting a culture of cybersecurity awareness among stakeholders. The study aims to provide actionable insights to strengthen the cybersecurity posture of Indian banks, thereby ensuring the safety and integrity of the banking ecosystem.